2022
DOI: 10.1039/d2sc90214a
|View full text |Cite
|
Sign up to set email alerts
|

A focus on the discovery of potent and selective cyclic peptide scaffolds for drug development

Abstract: Library-based screening methods such as mRNA display are paving the way for the discovery of cyclic peptides towards previously undruggable space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Modern display technologies such as phage, ribosome or mRNA display enable the rapid identification of potent and selective CP ligands, for subsequent use in biological experiments or drug discovery efforts. [1][2][3] In a previous study, we demonstrated the use of an efficient, high throughput strategy from next generation sequencing (NGS) hits to identifying high affinity CP binders. 4 In this study, we aimed to investigate different avenues to develop CP binders against a protein family, with differing target binding profiles which either interact with a target selectively or provide a specific interaction profile (binding to only a subset of targets).…”
Section: Introductionmentioning
confidence: 99%
“…Modern display technologies such as phage, ribosome or mRNA display enable the rapid identification of potent and selective CP ligands, for subsequent use in biological experiments or drug discovery efforts. [1][2][3] In a previous study, we demonstrated the use of an efficient, high throughput strategy from next generation sequencing (NGS) hits to identifying high affinity CP binders. 4 In this study, we aimed to investigate different avenues to develop CP binders against a protein family, with differing target binding profiles which either interact with a target selectively or provide a specific interaction profile (binding to only a subset of targets).…”
Section: Introductionmentioning
confidence: 99%